Photo‐Triggered Microcapsules. Issue 1 (February 2016) - Tylkowski, Bartosz; Giamberini, Marta; Underiner, Todd; Prieto, Susana Fernandez; Smets, Johan
Summary: Photosensitive microcapsules that reversibly switch upon visible light irradiation are attractive targets for drug delivery, fragrance release and pesticide delivery. In this study we report the development of visible light triggered microcapsules and demonstrate the concept of protection and remote release of a model, non‐toxic perfume oil. Polyamide microcapsule shells containing visible light‐sensitive ortho‐substituted azobenzene moieties in the main chain of the polymer were prepared by oil‐in‐water interfacial polymerization method. Microcapsules surface and cross‐section morphologies were observed by SEM. Triggered perfume release during light irradiation was monitored by means of GC/MS. We suggest that the mechanism of perfume release from the microcapsules shell is based on decrease of modified azobenzene length during light illumination. This visible light‐induced compression of microcapsules offers a new way to modulate the release of encapsulated materials.